Performance Analysis And Postulation Modeling Of Tool Wear In Drilling - Subramonian, Sivarao; Lee, Tian Soon; Chin, Chee Wen (2004)
Drilling Is the most important and frequency performed cutting procedure in the machining process. Metal removing process is becoming increasingly more complex, demanding and experiences an unprecedented growth. It has been reported that, one-third operation of material removal processes performed in industry is drilling operation. The paper deals with the measurement and the analysis of tool wear at different cutting conditions and parameters as per the model designed and tested according to factorial design method. Total of sixteen experiments were carried out to complete the research by using two different make twist drills (tool X and tool Y) possessing same specifications. The variables selected for tool wear were cutting speed, feed, machining time and thrust force. The designed model is to be tested by the R square analysis. The aim of the present work is to identify suitable parameters, the monitoring of which will enable the prediction of drill failure. The relative comparison of tool wear for tool X and Y is to be done by observed values and analytical values, namely by statistical analysis and inverse coefficient matrix method. Later, tool validation is to be carried out to verify which is the better tool (X or Y) by residual analysis.